Simulasi Kebijakan untuk Peningkatan Harga Ekspor T urunan Crude Palm Oil Indonesia: Analisis Sistem Persamaan Simultan - Odry Syafwil; Fitri Bunga Adelia (JOURNAL EDUCATIONAL OF NURSING(JEN), 2018)
Palm oil industries is one of the leading agroindustrial in Indonesia. Since the downstream palm oil industries began at the end of 2011, the export volume of Indonesian CPO derived increased continously. However, it’s export pric e decreased. Thus, the main objective of this research was to built a single policy simulation scenarios that could increase the export price of Indonesian CPO derivatives. This research used simultaneous analysis with T wo-Stage Least Square estimation method that consisted three endogenous variables, namely export price and export volume of Indonesian CPO derivative and real exchange rate of rupiah to US dollar. The estimation results show that the real exchange rate had positive effects on the volume and export prices of Indonesian CPO derivatives. In contrast, the export volume of Indonesian CPO derivatives had positive effect on the real exchange rate and negative effect on the export price. Meanwhile, export prices of Indonesian CPO derivatives had negative effect on real exchange rate but didn’t effect on the export volume. From the estimation and historical time reference was obtained three simulation scenarios which could increase the export price of Indonesian CPO derivatives, i.e. increase 4.0 percent of export tariff, 0.4 percent,of inflation, and 0.4 percent of BI real interest rate. However, each scenario also negative effect on certain endogenous variables. If export tariff of Indonesian CPO derivative was increased, the export volume would decrease. Meanwhile, if the inflation or B I real interest rate was increased, the real exchange rate would depreciate. Keywords: Simultaneous Analysis, 2SLS, Downstream, Export Price, CPO